New Legal Theory Concept: Integrative-Tetradic Realism Theory - Aris Prio Agus Santoso (The Easta Journal Law and Human Rights, 2025)
The absence of a legal theory that holistically integrates the four pillars legal certainty, substantive justice, social utility, and public participation, poses a key challenge in addressing the complexities of modern law, which is increasingly pluralistic and dynamic. This study aims to formulate and evaluate the Integrative-Tetradic Realism Theory as a new legal paradigm. Using a normative juridical method with a conceptual approach and theory-comparison techniques, the research develops a comprehensive and systematic synthesis relevant to contemporary legal dynamics. The results show that Integrative-Tetradic Realism offers a holistic and transformative paradigm, addressing limitations of classical theories such as positivism, natural law, realism, and Critical Legal Studies. By integrating normative, sociological, philosophical, and practical dimensions, and emphasizing its four pillars, this theory provides an adaptive framework that balances legal structures, moral values, social contexts, and public participation. It aims to create a legal system that is normatively valid, just, contextual, and responsive to societal changes. Acting as a bridge between ideal law and empirical reality, it offers a conceptual foundation for inclusive, ethical, and functional legal reform in modern society.